I am confused betweeen tangent plane to the level set(is it the same as level surface?) and to the tangent plane on the surface?

I know the formula $z=f(x,y): z-z_0 = f_{x}(x_0)(x-x_0) +f_y(y_0)(y-y_0)$ but cannot understand for which case it corresponds. Also I found some example where it was just without $z$ and $z_0$ : $f_{x}(x_0)(x-x_0) +f_y(y_0)(y-y_0)=0$

What whould be the difference between two tangent planes? It would be very nice if someone could explain it on the numerical example.


This one

$$z-z_0 = f_{x}(x_0)(x-x_0) +f_y(y_0)(y-y_0)$$

is the general expression for the tangent plane to $z=f(x,y)$ at the point $(x_0,y_0,z_0)$ while

$$f_{x}(x_0)(x-x_0) +f_y(y_0)(y-y_0)=0$$

is the intersection of the tangent plane with $x-y$ plane $(z=0)$ when $z_0=0$.

For example $z=f(x,y)=x^2+y^2 \implies f_x=2x \quad f_y=2y$ then at $(1,1,2)$ the tangent plane is


  • $\begingroup$ mathonline.wikidot.com/tangent-planes-to-level-surfaces Why then here in example 1 we do not write $w-16=2(x−1)+4(y−2)+2\sqrt11(z−\sqrt11)$? $\endgroup$ – Sally Mar 31 '18 at 8:42
  • $\begingroup$ @Sally we must refer to surface, that is an expression of this kind $z=f(x,y)$ that is $z-f(x,y)=0$. In example 1 we have $x^2+y^2+z^2-16=0$ and we are apply the same method. You should clarify why yhe formula by gradient works. $\endgroup$ – user Mar 31 '18 at 8:47
  • $\begingroup$ @Sally The key point is that the equation of a plane is given by $ax+by+cz+d=0$ where $(a,b,c)$ is a normal vector to the plane. $\endgroup$ – user Mar 31 '18 at 8:50
  • $\begingroup$ @Sally Now if we have a surface $F(x,y,z)=0$ the normal vector at $(x_0,y_0,z_0)$ is given by the gradient vector at that point that is $$F_x(x_0,y_0,z_0) \vec i + F_y(x_0,y_0,z_0) \vec j + F_z(x_0,y_0,z_0) \vec k$$. $\endgroup$ – user Mar 31 '18 at 8:53
  • 1
    $\begingroup$ @Sally Well done! What it matters is that you are aware about the theory behind. $\endgroup$ – user Mar 31 '18 at 9:02

Case $1)$ $$z= f(x,y)$$

Tangent plane is : $$z-z_0 = f_{x}(x_0)(x-x_0) +f_y(y_0)(y-y_0)$$

Case $2)$

$$ F(x,y,z)=0$$

The normal to the tangent plane is $$N=\nabla F =(\partial F/\partial x,\partial F/\partial y,\partial F/\partial z)$$ evaluated at $(x_0,y_0,z_0).$

The equation of Tangent plane is then,

$$ a(x-x_0)+b(y-y_0)+c(z-z_0)=0$$

where $N=(a,b,c)$ is the said normal vector.

Note that Case $2$ is a generalization of case $1$

We can wright $z= f(x,y)$ as $$ F(x,y,z)= z- f(x,y)=0$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.